Cambridge Vocabulary for First Certificate classroom vocabulary practice - Thomas B. Barbara (Cambridge Books for Cambridge Exams)
Are you preparing for the First Certificate Exam? Do you want to practise all the vocabulary you need э be confident in the exam? Cambridge Vocabulary for First Certificate covers the vocabulary that iccurs in the exam and provides the following: error warnings to help you avoid common mistakes regular tests to check your progresspractice exam tasks from the Use of English, Reading, Writing, Listening and Speaking papers useful tips on how to approach exam tasks techniques for learning and remembering vocabulary a full wordlist for easy reference vocabulary in a listening contextCambridge Vocabulary for First Certificate is informed by the lambridge International Corpus and the Cambridge Learner !orpus to ensure that vocabulary is presented in genuine ontexts and the book covers the errors students really make his book is suitable for the updated exam.